The Influence of Principal Leadership and Teacher Performance on the Quality of Education in Islamic Junior High Schools in Pematangsawa District - Hulaifah Hulaifah; Eka Fitria Ningsih; Wawan Wawan (Assyfa Journal of Islamic Studies, 2025)
This study aims to analyze the influence of principal leadership and teacher performance on educational quality in junior high schools (SMP/MTs) throughout Pematangsawa District, Tanggamus Regency. The method used was quantitative, with a sample of 54 respondents and multiple linear regression analysis. The results of the assumption test showed that the data were normally distributed, linear, and free from multicollinearity, autocorrelation, and heteroscedasticity. The results showed that principal leadership and teacher performance simultaneously had a significant effect on educational quality (F = 88.913; sig. 0.000 < 0.05). Partially, principal leadership had no significant effect (t = 1.232; sig. 0.224 > 0.05), while teacher performance had a positive and significant effect (t = 6.220; sig. 0.000 < 0.05). The Adjusted R Square value of 0.768 indicates a contribution of 76.8% between the two variables. Based on the research results, it can be concluded that teacher performance is the dominant factor in improving educational quality, while principal leadership has not yet had a significant direct impact. However, both variables together still contribute significantly to improving educational quality. Therefore, improving educational quality needs to focus on strengthening teacher performance supported by effective principal leadership.